Modeling of Simultaneous Denitrification - Anaerobic Digestion - Organic Matter Aerobic Oxidation and Nitrification in an Anoxic-Anaerobic-Aerobic Compact Filter Reactor - Huilinir-Curio, C (2012)
Sin Editorial Disponible